Attenuated SIV causes persisting neuroinflammation in the absence of a chronic viral load and neurotoxic antiretroviral therapy. (23rd October 2016) - Ferguson, Deborah; Clarke, Sean; Berry, Neil; Almond, Neil
Abstract : Objectives: Using simian models, where SIV chronic viral loads are naturally controlled in the absence of potentially neurotoxic therapies, we investigated the neuropathological events occurring during times of suppressed viraemia and when these events were initiated. Design: Cynomolgus macaques were infected with SIV strains that are naturally controlled to low levels of chronic viraemia. Study 1: animals were maintained up to 300 days after inoculation and analysed for viral-induced neuropathology following sustained suppression of chronic viral loads. Study 2: initiation and development of lesion was examined following 3, 10, 21, or 125 days SIVmacC8 infection. Methods: Formalin-fixed, paraffin-embedded brain sections were analysed following immunohistochemical staining for simian immunodeficiency virus (SIV) (KK41), blood–brain barrier leakage (ZO-1, fibrinogen), apoptosis (active caspase 3), neuroinflammation [GFAP, cyclooxygenase (COX)-1, COX-2], microglia and macrophage (Iba-1, CD68, and CD16), oligodendrocytes (CNPase1), MHC class II expression, and T cells (CD3 and CD8). Replicating SIV was detected through in-situ hybridization. Results: Study 1: neuroinflammation was present despite prolonged suppressed viraemia. Study 2: attenuated SIV entered the brain rapidly triggering acute phase neuroinflammatory responses. These did not return to naive levels and GFAP and COX-2 responses continued to develop during a chronic phase with a suppressed viral load. Conclusion: Neuroinflammatory responses similar to those in HIV neurocognitively impaired patients are present within macaque brains during prolonged periods of suppressed SIV viral load and in the absence of potentially neurotoxic antiretroviral drugs. These responses, initiated during acute infection, do not resolve despite the lack of on-going peripheral viraemia to potentially reseed the brain. Abstract : Supplemental Digital Content is available in the text